Modelling of transport mechanisms and drying shrinkage for multilayer ceramic membrane structure - Harun, Zawati; Tze, Ching Ong; Matsuura, Takeshi; Hubadillah, Siti Khadijah; Dzarfan Othman, Mohd Hafiz; Ismail, Ahmad Fauzi (ScienceDirect, 2018)
In ceramic membrane preparation, the understanding of drying phenomena is very important to ensure no defects and failures that may present in the membrane layers. The combination of hygroscopic and non-hygroscopic multilayer systems that possess different properties is always associated with the failure ofthe consolidated structure of ceramics during the drying and sintering process. Hence, a two-dimensional mathematical model that coupled mass, heat, and gas transfer was employed to describe the drying process as a whole multilayer ceramic membranes structure. The finite element method was used to solve the model and computation was carried out using a Skyline solver to capture the highly nonlinear and transient process. This study emphasises on the evolution of transport variables during the drying that can be correlated to shrinkage mechanism. The side surface heating boundary was performed with a conclusion that hygroscopic materials have low drying rate due to the material characteristic which inherent higher water retention in a solid matrix. This characteristic also causes higher pore water pressure and gas pressure. The drying of hygroscopic layer has resulted in higher moisture gap which in turn increased the possibilities of cracking. The results obtained from this study enable the optimisation with respect to drying time and material selection thus significantly contributes to the energy saving as well as reducing the environmental effect via less waste energy loss.